Pengaruh Kompetensi Profesional terhadap Kinerja Guru di MI Tawakkal Denpasar Bali Tahun Pelajaran 2019/2020 - Jailani, Firman; Ade F, Novena; Arifin, Haris Nursyah (Faidatuna, 2022)
Professional competency means broad and in-depth mastery of learning material which includes mastery of curriculum subject matter. There are several factors that influence teacher performance, one of which is teachers who need guidance to become professional teachers. the aim of this research is; (1) To determine the significant influence of professional competence on teacher performance at MI Tawakkal Denpasar Bali; (2) determine the contribution of professional competence to the performance of MI Tawakkal Denpasar Bali teachers. This research is quantitative research in determining samples using a saturation formula with results of 38 samples. The data collection technique used in this research is using a questionnaire and analysis techniques using Simple Linear Regression. The research results show that: 1) there is a positive and significant influence of professional competence on the performance of MI Tawakkal Denpasar Bali teachers. This is shown by the professional competency variable which has a positive regression coefficient on performance of 34,599, which means that if professional competency increases by 1 point, performance will increase by 34,599. 2) the professional competency variable (X) has a simultaneous contribution of 18.1% to the teacher performance variable (Y) and the remaining 81.9% is influenced by other factors not researched by the author.